As interrelações entre direito e religião na sociedade funcionalmente diferenciada - Zuchetto, Lisiane da Silva (2019)
This dissertation is part of the Research Line “Constitutional Jurisdiction and Democracy” of the Master's Course, in the context of its area of concentration “New Law Paradigms”. The research seeks to observe contemporary society from the systemic point of view, beginning the study by the system of religion. Considering specifically the model of secular state in the Brazilian territory, the social function of religion was analyzed, as well as in which way its communication occurs, from the systemic point of view. Social complexity can give rise to constitutional problems related to fundamental rights and human rights or to control and limitation of power, reflected in the decisions of the Legislative and Judiciary powers, thus involving the political system and the juridical system. In the search for solutions to these constitutional problems, systemic coalitions may occur, which can lead to the destruction of a certain system. In this way, the possible interconnection of these different social systems involves the questioning of the research that is precisely the possibility of this connection between systems in the model of the secular state, especially in the Brazilian State. Resorting to the systemic method, which through the communication between these different social systems form the society, the constitution represents an element that can help in the solution of the problem. In this context, the constitution acts as a link between systems, that is, in the form of structural linkage, providing the connection between different systems. This connection allows these systems to dialogue among themselves in the s earch for a solution to the constitutional problems presented. Therefore, the structural linkage leads to the transconstitutionalism, which is a reciprocal learning between different legal orders. In the transconstitutionalism it is possible for several le gal orders to find a solution to constitutional problems through the exchange of learning with the so-called transition bridges.